(untitled) (مجلة العلوم الشاملة, 2025)
This study examines the relationship between engineering project performance and the strategic orientation of engineering firms operating within the Libyan local market. Specifically, it investigates how key performance indicators—namely cost control, time management, quality outcomes, and client satisfaction—inform and influence long-term strategic decision-making processes. Adopting a mixed-methods research design that integrates both quantitative survey data and qualitative insights from expert interviews, the study identifies core challenges and advances evidence-based recommendations aimed at aligning project execution with strategic development objectives in Libya’s post-conflict, infrastructure-driven economy. The findings reveal that only 36% of engineering projects in Libya are completed within their originally scheduled timeframes, while 42% experience substantial cost overruns. Nonetheless, 58% of projects are reported to meet acceptable quality standards, and 61% achieve moderate to high levels of client satisfaction. Statistical analysis indicates a strong positive correlation (r = 0.72) between overall project performance and firms’ strategic responsiveness, particularly in the domains of innovation, client orientation, and adaptability to market fluctuations. Moreover, 70% of the surveyed firms acknowledged that project outcomes significantly influence their strategic planning. There is an observable shift among these firms from traditional cost-leadership strategies toward approaches that prioritize quality enhancement and client engagement. High-performing firms are also more inclined to adopt digital transformation initiatives, invest in human capital development, and diversify their service portfolios. The study concludes that enhancing engineering project performance is essential for firms seeking to improve their strategic positioning within Libya’s dynamic construction and infrastructure sector. To achieve sustainable growth, the research recommends targeted investments in project management competencies, the adoption of advanced digital technologies, the reform of existing regulatory frameworks, and the promotion of collaborative public-private partnerships.